The dignity of a person dying of moral obligation in medicine - Czekajewska, Justyna (Studia Ecologiae et Bioethicae, 2018)
In the Christian tradition, the concept of ‘dignity’ derives from natural law. According to St. Thomas Aquinas, every human being preserves inherent dignity throughout life because it comes from God. In line with this thought is the view that the gift of dignity cannot be taken away. Even various forms of aggression and hatred are not capable of destroying humanity; in other words, they cannot deprive man of this most precious value. In the interest of spiritual development, philosophers and theologians urge adherence to moral standards. Actions based on an ethical foundation teach responsibility and thus are important to respect. This article on human dignity explores these ideas through the example of medical care for chronically and terminally ill patients. I not only focus on palliative care but also explain how to care for a dying person while respecting his or her rights as a patient, especially the right to a decent and peaceful death.